Antiviral actions of flavanoid-derived compounds on dengue virus type-2. - Muhamad, M.; Kee, L.Y.; Rahman, N.A.; Yusof, R. (Ivyspring International Publisher, 2010)
Dengue viruses, mosquito-borne members of the Flaviviridae family, are the causative agents of dengue fever and its associated complications, dengue haemorrhagic fever and dengue shock syndrome. To date, more than 2.5 billion people in over 100 countries are at risk of infection, and approximately 20 million infections were reported annually. There is currently no treatment or vaccine available for dengue infection. This study employed a whole-cell organism model or in vitro methods to study the inhibitory property of the flavanoid-derived compounds against DENV2 activity. Results showed that at concentration not exceeding the maximum non-toxic dose (MNTD), these compounds completely prevented DENV2 infection in HepG2 cells as indicated by the absence of cytophatic effects. The in vitro antiviral activity assessed in HepG2 cells employing virus inhibition assay showed high inhibitory activity in a dose dependent manner. At concentration below MNTD, compounds exhibited inhibitory activity against DENV2 with a range of potency strengths of 72% to 100%. The plaque forming unit per ml (pfu/ml) was reduced prominently with a maximum reduction of 98% when the infected HepG2 cells were treated with the highest non-toxic dose of compounds. The highly potent activity of the compounds against DENV2 infection strongly suggests their potential as a lead antiviral agent for dengue.